Dampak Zakat Terhadap Perubahan Tipologi Kemiskinan di Kota Palembang - Dwi Septa Aryani; Yuni Rachmawati; Agung Anggoro Seto (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2019)
This research aims to find out if the charity had an impact on the change of the poverty of the typology recipient of zakat (Mustahik) in Palembang. The population in this research is all Mustahik in Palembang of 15.862 people. Sampling techniques using Accidental Sampling by the number of samples was determined as many as 200 respondents. The data type used is quantitative data. The primary data source, this research uses the Cibest Model, data analysis techniques using paired sample t-test. The results showed that the zakat to changes impacting the typology of poverty on Mustahik in the city of Palembang with Significance value 0.000. Where before accepting zakat, there are only two types of Mustahik poverty in the city of Palembang which is absolute poverty (poor material and spiritual) as much as 71.5%, and material poverty as much as 28.5%. However, after receiving zakat, Mustahik's type of poverty turned into material poverty as much as 54.5%, the absolute poverty of 24.0%, the spiritual poverty of 4.5% and there was 17% Mustahik who had been prosperous after receiving Zakat. This research also proves that zakat is effective to play a role in reducing the poverty of Mustahik in Palembang.